A Stroll Through the History of Monoxenous Trypanosomatids Infection in Vertebrate Hosts - Boucinha, Carolina; Andrade-Neto, Valter Viana; Ennes-Vidal, Vítor; Branquinha, Marta Helena; Santos, André Luis Souza dos; Torres-Santos, Eduardo Caio; d’Avila-Levy, Claudia Masini (Frontiers in Cellular and Infection Microbiology, 2022)
The Trypanosomatidae family encompasses unicellular flagellates and obligate parasites of invertebrates, vertebrates, and plants. Trypanosomatids are traditionally divided into heteroxenous, characterized by the alternation of the life cycle between an insect vector and a plant or a vertebrate host, including humans being responsible for severe diseases; and monoxenous, which are presumably unique parasites of invertebrate hosts. Interestingly, studies reporting the occurrence of these monoxenous trypanosomatids in humans have been gradually increasing, either associated with Leishmania co-infection, or supposedly alone either in immunocompromised or even more sporadically in immunocompetent hosts. This review summarizes the first reports that raised the hypothesis that monoxenous trypanosomatids could be found in vertebrate hosts till the most current reports on the occurrence of Crithidia spp. alone in immunocompetent human patients.